Extremely strong tubular stacking of aromatic oligoamide macrocycles. Issue 1 (26th September 2014) - Kline, Mark A.; Wei, Xiaoxi; Horner, Ian J.; Liu, Rui; Chen, Shuang; Chen, Si; Yung, Ka Yi; Yamato, Kazuhiro; Cai, Zhonghou; Bright, Frank V.; Zeng, Xiao Cheng; Gong, Bing
Abstract : Aromatic oligoamide macrocycles 3 undergo extremely strong stacking in both solution and the solid state, forming tubular assemblies that further aggregate. Abstract : As the third-generation rigid macrocycles evolved from progenitor1, cyclic aromatic oligoamides3, with a backbone of reduced constraint, exhibit extremely strong stacking with an astoundingly high affinity (estimated lower limit of K dimer > 10 13 M −1 in CHCl3 ), which leads to dispersed tubular stacks that undergo further assembly in solution. Computational study reveals a very large binding energy (−49.77 kcal mol −1 ) and indicates highly cooperative local dipole interactions that account for the observed strength and directionality for the stacking of3 . In the solid-state, X-ray diffraction (XRD) confirms that the aggregation of3 results in well-aligned tubular stacks. The persistent tubular assemblies of3, with their non-deformable sub-nm pore, are expected to possess many interesting functions. One such function, transmembrane ion transport, is observed for3 .